Japan's Food Security Issues: A Geopolitical Challenge for Africa and East Asia? - Thomas Feldhoff (Journal of Global Initiatives, 2015)
Japan’s food self-sufficiency ratio is remarkably low compared to other industrialized nations. Growing world population, food, water, and energy shortages in combination with climate change and the rising competition for the world’s limited resources are the transnational dimensions of food and nutrition security related risks that are already affecting Japan. This paper analyzes the development and institutional context of Japanese policies related to its food security, particularly in relation to its commitments to support developing countries and to promote food security in Africa. One dimension of particular interest is the Japanese engagement in large-scale land investments in Africa. ProSAVANA, Japan’s most ambitious initiative in its development cooperation with African countries is introduced as a case study. The international context of examining Japan’s large-scale land investments highlights the fluctuation between its commitments to contribute to international development policies and the more narrow-minded pursuit of its national interests and intensified efforts to strengthen its position in international politics in relation to powerfully emerging China.